Intraespecific variation in drought resistance of nothofagus antarctica (g. Forst.) Oerst. (nothofagaceae) - Piper, Frida I.; Zuniga-Feest, Alejandra (EDICIONES UNIV, CONCEPCION, 2016)
1 FONDECYT fpiper@ciep.cl 2 FONDECYT 69